Prevenção de incêndio em edificações acima de 6 pavimentos com mais de 20 anos na região central de Apucarana - Espanhol, Roger Alex (2015)
Taking into account the danger and damage a fire can do, a concern about the ways to prevent it and extinguish it is very important. The following work has the objective to show how the standard of prevention and fire fighting deals with many related items such as: the access of the fire trucks, emergecy exits, fire brigade, emergency lights, fire alarm, emergency sinalization and the presence of fire entinguisher and hydrants.Demonstrating the main inadequacies and difficulties related to these elements, from the buildings which were constructed over 20 years ago, when we were under another prevention code to the current code, which came into effect in 2012, having as reference the São Paulo prevention code. The building on focus in this research are the ones over 6 floors, classified as A2 due it’s residencial use, in the central region of Apucarana, in this category were visited 22 within aproximadely 40 buildings (Estimated number by the Apucarana’s city hall responsable Engineer Herivelton Moreno).Based on the field research, studies on the matter, previous and current codes analysis with instrutions of professionals on the field. All the incompatibilities with the current law were listed, quantifying it, so it can be observed the most frequent and biggest risks. The fire sinalization, emergency exits, inconformities related to prevention projects apear constantly in the analysis, beeing indentified as the main reason of the irregularity, wherein at least one of them is present in 91 % of cases.Even with an evolution of the buildings with the fire instrutions, there are still many irregularities remaining and neglect with the abordations about the matter. Even that history show us how devastating can be it is event, there is not a united regulation for the entire country.